Porous ZnO Nanosphere Inherently Encapsulated in Carbon Framework as a High-Performance Anode For Ni–Zn Secondary Batteries - Li, Zhuo; Hu, Xianwei; Kang, Jian; Wang, Xiaoli; Kong, Lingyu; Shi, Zhongning; Wang, Zhaowen (Frontiers in Chemistry, 2022)
Nickel-zinc (Ni-Zn) secondary battery that is environmentally friendly and inexpensive has been regarded as a promising rechargeable battery system. However, the generation of deformation and dendrites of the traditional zinc anode during the cycling can cause capacity degradation and impede its practical application. Herein, we design a hierarchical ZnO nanosphere coated with an inherently derived ZIF-8 porous carbon shell (ZnO@CZIF-8) through a simple controllable method. The conductive carbon shell and porous ZnO core can provide more active sites, allow the fast transfer of electron, and buffer the volume expansion of the electrode effectively. Benefiting from the synergistic effect amid the inherently ZIF-8 derived carbon shell and ZnO core, ZnO@CZIF-8 nanospheres exhibit a satisfied capacity of 316 mAh g-1 at the current density of 1 A g-1 after 50 cycles and outstanding rate capacity when worked as the anode for Ni-Zn secondary battery with merchant agglomerative Ni(OH)2 as the cathode. These results imply that ZnO@CZIF-8 nanosphere is a hopeful anode for high-energy Ni-Zn secondary battery.